Newborn mid-upper arm circumference as valid proxy measure of gestational age - Agrawal, Ankit; Gaur, Ajay; Ambey, Ravi (Indian Journal of Child Health, 2020)
Background: Prematurity is a significant contributor to neonatal mortality in India. Conventionally, gestational age (GA) of newborn is estimated using Naegele’s formula and New Ballard scoring (NBS), a physical and neurological maturity scoring method of newborn. Objective: The current study was aimed to find out an estimation of GA using neonatal mid-upper arm circumference (MUAC). Materials and Methods: This hospital-based prospective observational study was conducted in the sick newborn care unit and postnatal ward of a tertiary hospital of Central India. A total of 1303 newborns were included in the study. The MUAC was taken and the GA assessed by NBS and Naegele’s formula was filled in a pro forma. Results: A total of 1303 neonates were evaluated. The mean MUAC varied from 6.20±0.5 cm among the preterm newborns to 10.27±0.5 cm among newborns born after the 40th week of gestation. The mean MUAC was 8.04±0.6 cm irrespective of GA. MUAC was found to be significantly correlated with GA (r=0.903, p<0.01). Conclusion: MUAC in newborns can be used as surrogate of GA and can be used for its estimation.